ANALISIS BAURAN PEMASARAN PADA UMKM (STUDI KASUS PADA UMKM ENTING-ENTING GEPUK DI KOTA SALATIGA) - Viona Ayudhia; Wahyu Hidayat (Universitas Diponegoro, 2017)
Nowadays, the growth of Small Medium Enterprises (SMEs) in Indonesia is emerged it was caused by the growing business in micro-small scale, which is one of them is enting-enting gepuk enterprises in Salatiga. Nevertheless, in conjunction with the emegence of enting-enting gepuk enterprises, the competition among the similiar products or the subtitution products was triggered. The competitions of various brands of enting-enting gepuk have allowed the improvement in marketing strategy for each SMEs enting-enting gepuk. One of the marketing strategies to support the product promotion in order to satisfy the consumers is marketing mix.This research is aimed to know the marketing mix which is implied by enting-enting gepuk enterprises in Salatiga. This research used descriptive analysis, with interviews and observations as its data collection technique. Data sample technique used purposive method. Sample of this research is 5 (five) respondents who are the owner of enting-enting gepuk enterprises in Salatiga.This research concludes that enting-enting gepuk enterprises in Salatiga have did the innovation on product design by adding the choice of flavor variant and change the product packaging design, technical innovation in the form of machine use, product development by producing product besides enting-enting gepuk. Pricing strategies by offering products at different prices based on the amount of contents in a single pack. Promotional strategies tend to be passive. Distribution strategies use direct marketing channels. Based on the aforementioned statements, the researcher suggested that the owner of enting-enting gepuk enterprises can improve their creativities to create new innovations, create a product with a smaller amount of content in one package so the price set more affordable, improve the product promotion with social media or online sites to expand the market, improve the cooperation with the distributor or shops that located throughout Indonesia.